Enhancing Manufacturing Sustainability: The Impact of Green Supply Chain Integration and Total Quality Management on Firm Performance in Karawang - Jauhari Arifin; Iman Sudirman; Ester Manik; Sutrisno (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study has an objective to examine the effect of green supply chain integration (GSCI) and total quality management (TQM) practices on company performance in manufacturing companies in Karawang Regency, West Java, Indonesia. This study estimates that GSCI and TQM each have a positive and significant impact on company performance. It applies a quantitative approach. The primary data were collected through structured questionnaires distributed to operational managers of selected manufacturing companies, using sector- and scale-based sampling. The variables utilized include GSCI and TQM as independent variables and company performance as the dependent variable. The data were analyzed using Structural Equation Modeling (SEM) to test validity, reliability, and causal relationships. The results indicated that GSCI (β = 0.550; t = 10.214) and TQM (β = 0.509; t = 9.100) significantly and positively affect company performance, with an R² of 0.739, indicating strong explanatory power. These findings suggest that integrating environmental practices into the supply chain and implementing continuous quality improvement can enhance operational and organizational outcomes. This study advocates that sustainability policies in industrial parks should prioritize operational integration and quality management. Future research could explore mediating variables and longitudinal designs to assess the long-term impact of sustainability.